Impact of persistent, frequent regurgitation on quality of life in heartburn responders treated with acid suppression: a multinational primary care study. Issue 10 (5th April 2013) - Kahrilas, P. J.; Howden, C. W.; Wernersson, B.; Denison, H.; Nuevo, J.; Gisbert, J. P.
Summary: Background: In gastro‐oesophageal reflux disease (GERD), heartburn responds well to acid suppression, but regurgitation is a common cause of incomplete treatment response. Aim: To assess the prevalence and burden of persistent, frequent regurgitation in primary care patients with GERD treated with acid suppression. Methods: We analysed observational data from 134 sites across six European countries in patients diagnosed with GERD. Within 3 months of the index visit, symptoms were assessed using the Reflux Disease Questionnaire, and their impact on sleep and work productivity with the Quality of Life in Reflux and Dyspepsia questionnaire and the Work Productivity and Activity Impairment Questionnaire, respectively. Patients provided information on concomitant over‐ the‐ counter (OTC) GERD medication use. Results: Persistent, frequent (3–7 days/week) regurgitation was reported by 13.2% (153/1156) of GERD patients with no heartburn on acid suppression; the prevalence was very similar for patients with up to 2 days/week of ongoing mild heartburn. Among patients without heartburn, sleep disturbance of any type was reported by 50.7–60.1% with persistent, frequent regurgitation, compared with 38.1–51.1% and 14.4–19.2% of those with less frequent or no regurgitation respectively. Persistent, frequent regurgitation was associated with increased use of OTC medication and more hours of work missed, whether mild, infrequent heartburn was present or not. Conclusions: Frequent regurgitation, which persisted in 12–13% of patients with no or infrequent, mild heartburn on acid suppression, negatively affected sleep and work productivity, and increased use of OTC medication. Persistent, frequent regurgitation is problematic for primary care patients with GERD.